2011
DOI: 10.3168/jds.2010-4137
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of heat shock protein genes and their splice variants in bovine preimplantation embryos

Abstract: Heat shock proteins (HSP) are among the first proteins produced during embryonic development and are crucial to cell function; their activities include folding, unfolding, transport, and localization of proteins and differentiation and regulation of the embryonic cell cycle. Although HSP have been extensively studied in humans and mice, limited information exists on the roles of these genes in bovine embryos. As such, the objectives of this study were to profile the expression of HSP and their splice variants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 32 publications
1
33
0
1
Order By: Relevance
“…Lund et al (2001) observed that forms of HSP22 resulted from alternative intron splicing in maize (Zea mays). Zhang et al (2011) reported that 13 HSP genes had one transcript each, two genes had two transcripts each, and two had three transcripts each in bovine. Heat stress-AS occurs in transcripts for specific functions.…”
Section: As Acts As An Important Posttranscriptional Regulation In Grmentioning
confidence: 99%
“…Lund et al (2001) observed that forms of HSP22 resulted from alternative intron splicing in maize (Zea mays). Zhang et al (2011) reported that 13 HSP genes had one transcript each, two genes had two transcripts each, and two had three transcripts each in bovine. Heat stress-AS occurs in transcripts for specific functions.…”
Section: As Acts As An Important Posttranscriptional Regulation In Grmentioning
confidence: 99%
“…Previous studies have indicted that HSPs may play important protective roles in animal embryonic development. Zhang et al (19) found that more than ten HSP genes had differential expression between degenerate cattle embryos and blastocysts, whereas others were not expressed at all. This suggests the important roles of HSPs in fertilization and early development of the embryo.…”
Section: Discussionmentioning
confidence: 99%
“…In cattle, performance differences have been identifi ed in Bos indicus breeds and genetic polymorphisms in HSP70 have been associated with reproductive performance (Rosenkrans et al, 2010). In Holstein cows, differences in expression of genes in the HSP40 family have been associated with improved early embryonic development in vitro, indicating that these proteins may have a greater role in reproductive effi ciency than thought, even in animals not adapted to a tropical environment and not placed in a heat stress situation (Zhang et al, 2011). The speakers at this Physiology and Endocrinology Symposium were identifi ed to address these topics based on their research.…”
mentioning
confidence: 99%